Implications of the Mechanism of Change for the Decision-making Process in Environmental Protection - Embros, Grzegorz (Studia Ecologiae et Bioethicae, 2022)
Activities for environmental protection induce the necessity of adopting specific solutions aimed at their facilitation or enhancing their effectiveness. While implementation of new technological solutions seems quite obvious here, the need to develop specific solutions aimed at improving the decision-making process is frequently overlooked. Hence, proper identification of mechanisms that may reduce or significantly impair the effectiveness of these activities or lead to defined side effects is becoming of vital importance. In view of the above, the article will present selected cases which are subject to the mechanisms of change characterized by Neil Postman in Technopol. The first will be a direct reference to the process of generating changes by new technological solutions described by this author. The second, will draw on selected publications by Ulrich Beck and Gernot Böhme dealing with social phenomena or anthropological situations inscribed in that mechanism. The main task will therefore consist in tracing an analogy between the two characterized cases. In particular, the author will make an attempt to analyse the impact of the resulting consequences on the shape and course of the decision-making process, which is the aim of the present study. It seems that the preferences and choices with respect to certain solutions are conditioned by the anthropological profile of the decision-maker, but that at the same time they reciprocally induce his change. This, in turn, has an impact on the way of designing and formulating the principles of conduct in the field of environmental protection.